Psoriasis in hyper IgE syndrome – a case report - Ghaffari, Javad (Babol University of Medical Sciences, 2013)
Background: Hyper IgE syndrome (HIES) is a rare primary immune deficiency, described as Job(`)s syndrome characterized by increased serum levels of IgE, eczema, recurrent cutaneous and pulmonary infections. In this paper, we presented a case of Hyper IgE syndrome. Case Presentation: A 16-year-old Iranian boy presented with a one year history of skin lesions in knees and elbows was diagnosed of psoriasis disease. He had a history of recurrent infections including otitis media, pneumonia, diarrea and skin infection. Laboratory results showed increased level of total IgE and normal in other immunoglobulin. Histologic finding showed hyperkeratosis, parakeratosis of acanthotic epidermis with regular elongation of rete ridges diagnose psoriasis disorder. Conclusion: In conclusion, this is the first case of hyper IgE patient with psoriasis disorder. We addressed the important laboratory findings and actual theories explaining possible association between hyper IgE immunoglobulinemia and psoriasis disorder.